Analisis Pengaruh Faktor-Faktor Lingkungan Kerja Terhadap Kinerja Karyawan Dengan Metode Partial Least Square (PLS) Di PT. Benua Indah Tuban - Ana Zul Fia; Sunardi Sunardi; Tranggono Tranggono (UPN Veteran Jawa Timur, 2022)
Human resources are one of the production factors that have an important role in a company because they have very specific characteristics compared to other factors. PT. Benua Indah Tuban is a manufacturing company producing clay which is used as a basic ingredient for fertilizers. In its operational activities, workers in this company interact a lot with the same work environment with changing conditions. Employee performance of PT. Benua Indah Tuban during the months January-October 2020 experienced a decline. Thus it is necessary to study the influence of work environment factors on the performance of employees of PT. Benua Indah so that it can improve the performance of employees in the production department. This study uses the social environment, physical environment, and organizational environment as factors that affect employee performance. For data analysis, a model test using the Smart PLS application is used. This research method uses 50 samples with a sample as well as a population or what is called a saturated sample. The results of this study indicate that the physical environment variables have a significant effect on performance by 64.2% and the organizational environment has a significant effect on performance by 28.6%. While the social environment variable does not significantly influence the performance of -3.9%. The prediction model from the results of this study is able to explain the customer satisfaction variable by 63.2% (R2 = 0.632).